A supramolecular nano-delivery system based on AIE PARP inhibitor prodrug and glycosylated pillar[5]arene for drug-resistance therapy. Issue 79 (15th September 2022) - Yang, Manman; Yang, Ke; Gao, Bingling; Wang, Peng; Li, Tianjiao; Zheng, Yi; Pei, Yuxin; Pei, Zhichao; Lv, Yinghua
Abstract : A supramolecular nano-delivery system based on glycosylated pillar[5]arene (GP5) and an amide linked fluorescent DNA repair enzyme inhibitor (Pro-ANI) with the AIE effect was constructed for drug uptake visualization and drug-resistance therapy. Abstract : A supramolecular nano-delivery system GP5⊃Pro-ANI based on the host–guest complex of glycosylated pillar[5]arene (GP5) and an amide linked fluorescent PARP inhibitor (4-amino-1, 8-naphthimide, ANI) was constructed. The PARP inhibitor ANI, capable of inhibiting the ability of DNA damage repair, was modified into an AIE prodrug (Pro-ANI), which allows for the visualization of real-time cancer cellular drug uptake tracing and selective drug release. In vitro studies revealed that the DOX-loaded GP5⊃Pro-ANI achieved targeted drug delivery and dual-drug synergistic chemotherapy for DNA repair interference and tumor DNA collapse aggravation, which enhanced the chemosensitivity and overcame tumor drug resistance and migration. This strategy paves a new avenue for utilizing PARP inhibitors to construct AIE supramolecular nano-delivery systems for drug uptake visualization and synergistic chemotherapy.